Skin Micrograph Protector in a Burn Wound: Alloderm or Hydrogel Coating? - I. Yu. Arefyev; M. G. Ryabkov; V. V. Beschastnov; M. L. Bugrova; K. S. Petrova; P. V. Peretyagin; L. B. Timofeeva; A. A. Karpenko; A. A. Tulupov; N. A. Koloshein (Неотложная медицинская помощь, 2022)
AIM OF STUDY Was to compare the dynamics of engraftment of skin micrographs in a burn wound when using protectors from an allodermal graft and from a hydrogel coating.MATERIAL AND METHODS The experimental study was conducted on 18 rats with a scab formed 3 days after modeling a deep burn with an area of 20% of the body surface. Partial fascial necrectomy was performed: two rounded sections of the sling with a diameter of 25 mm were excised. 6 automicrographs of skin 4x4 mm, 0.3 mm thick, were applied to each surface freed from the scab. In each animal, micrographs on one of the wounds were covered with a hydrogel protector, on the other with an allodermotransplant from another animal of the group. A secondary aseptic dressing was applied to the protectors. On the 5th and 20th days after the operation, the state of micrographs was studied: blood circulation — according to laser Doppler flowmetry, microstructure in vivo — using optical coherence tomography, microstructure ex vivo — according to histological examination of biopsies.ReSUlTS Differences in the rate of restoration of blood circulation of micrographs in the early stages of the postoperative period were found. In the first 5 days, the perfusion of micrographs under an allodermal protector exceeded the indicator in micrographs under a hydrogel coating by 44 [21; 51] % (p=0.031) due to the contribution of endothelial and neurogenic mechanisms of blood flow modulation. Starting from day 10, the differences in perfusion were levelled, but there were signs of more active endothelial regulation of blood flow under the skin (p=0.028). Histologically, the appearance of full-blooded capillaries was revealed earlier in micrographs under the alloderm than when using a hydrogel protector. By 20 days, under the condition of regular change of hydrogel coatings, the area of wound healing under the studied coatings did not significantly differ. However, the structure of the integumentary tissue under the alloderm according to the optical coherence tomography data was closer to normal skin than when using a hydrogel protector.CONClUSIONS From the point of view of the physiology of the wound process, alloderm is the preferred option of an autograft protector in comparison with a hydrogel coating, which is probably due to the paracrine biological activity of the alloderm. However, hydrogel coatings can provide a comparable level of efficiency, provided they are regularly changed and, potentially, given the properties of cytokine activity.